Implementasi Kebijakan Pelayanan Kartu Identitas Anak di Kecamatan Kotapinang pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Labuhanbatu Selatan - Ilma Suryani Siregar; Budi Hartono; Dumasari Harahap (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to determine the implementation of the Child Identity Card (KIA) service policy in Kotapinang District at the Department of Population and Civil Registration, South Labuhanbatu Regency, North Sumatra Province and to identify and analyze the factors that influence it. The form of this research belongs to descriptive research that uses qualitative data analysis, namely this research is investigated by observation or observation, interviews, and describes the state of the object of research based on the facts. There were 18 informants in this study. Data collection techniques were obtained from interviews, observations, and documentation. While the data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that the implementation of the Child Identity Card (KIA) service policy in Kotapinang District at the Population and Civil Registration Office of South Labuhanbatu Regency, North Sumatra Province has not gone well. This is due to a lack of knowledge, perception, physical condition, gender and community living environment, lack of human resources in charge of services, lack of a special budget allocated for service equipment, frequent network disturbances so that the Standard Operational Service (SOP) is set. has been determined for 3 days sometimes not fulfilled.